Language Teaching: A Comparison of Social Representations Held by Fi Rst-And Fi Fth-Year Students of the Translation Studies Undergraduate Programme at Universidad de Santiago de Chile [Enseñanza de Lenguas: Una Comparación de Las Representaciones Sociales de Alumnos de Primer y Quinto Año de la Carrera de Lingüística Aplicada a la Traducción] - Rubio-Manriquez, M; Singer-Contreras, N; Rubio-Martin, R (Pontificia Universidade Catolica de Sao Paulo, 2019)
This article compares the social representations about the processes of teaching and learning a foreign language held by fi rst-and fi fth-year students of the translation studies undergraduate programme at Universidad de Santiago de Chile (USACH). The concept of social representations is taken from social psychology (Jodelet 1988, 2008; Moscovici 1979). A word association task and a semi structured interview were administered to four groups of translator trainees. Results show signifi cant changes in terms of language profi ciency, teaching and learning. It is concluded that such changes would promote the adoption of new methodologies for the foreign language course units in this translation programme. © 2019 Pontificia Universidade Catolica de Sao Paulo.